Optical Properties of Polyvinyl Alcohol doped with CoCl2 - Rizk, M.S. (Asian Journal of Chemistry, 2010)
Optical absorption measurements in the spectral range 4000–50000 cm–1 were performed on cast thin films of polyvinyl alcohol(PVA) and its composites with cobalt chloride (CoCl2). Identification of the structure and assignments of energy bands have been derived in terms of the ligand field theory. A mechanism based on the equilibrium between six-coordinated and four-coordinated symmetry is proposed to account for the obtained spectra. Such equilibrium is attributed to a small difference between the stabilization energies, and the symmetry is found to be altered with cobalt chloride concentrations.